A framework for conflict analysis in spatial planning for tourism. (October 2017) - Almeida, Joana; Costa, Carlos; Nunes da Silva, Fernando
Abstract: The perspectives of diverse stakeholders on spatial planning and tourism development, on one hand, and natural values conservation, on the other, often lead to conflicts. An in-depth analysis of the sources of conflict is crucial for developing the appropriate strategies to manage them. This paper specifically addresses the current conflicts between tourism development and land use planning and natural values management. For this purpose, a case study was carried out on the Troia-Melides Coast (Portugal), a coastal area rich in natural values and currently under pressure from real estate and tourist developers. Interviews were carried out with 26 key-stakeholders. Based on the theoretical framework of Moore's model, a broad and integrated overview of these conflicts is presented. Conflicts are categorized as follows: institutional organization, public policies and legislation, power, others structural constraints (e.g. time and resources), information and stakeholders' interests, values and relationship. Highlights: Integrated conflict analysis is key to the conflict management process preparation. The absence of a land use policy is the main problem in tourism planning conflict. Unclear nature conservation strategies are main sources of conflict. Although being crucial, there is not an effective power conflict mediation. Information and empowerment of public authorities are key to conflict management.